Renal hyperparathyroidism- a risk factor in the development of encapsulating peritoneal sclerosis - Moinuddin, Zia; Wang, Kelvin; Fullwood, Catherine; Wiredu, Elizabeth; Hutchison, Alastair; Vardhan, Anand; Herrick, Sarah E.; Summers, Angela; Augustine, Titus; van Dellen, David (Frontiers in Endocrinology, 2024)
Background: Encapsulating peritoneal sclerosis (EPS) is a rare complication of prolonged peritoneal dialysis (PD) exposure, characterised by peritoneal thickening, calcification, and fibrosis ultimately presenting with life-threatening bowel obstruction. The presence or role of peritoneal calcification in the pathogenesis of EPS is poorly characterised. We hypothesise that significantly aberrant bone mineral metabolism in patients on PD can cause peritoneal calcification which may trigger the development of EPS. We compared the temporal evolution of bone mineral markers during PD in EPS patients with non-EPS long-term PD controls. Methods: Linear mixed model and logistic regression analysis were used to compare fourmonthly serum levels of calcium, phosphate, parathyroid hormone, and alkaline phosphatase (ALP) over the duration of PD exposure in 46 EPS and 46 controls (PD, non-EPS) patients. Results: EPS patients had higher mean calcium (2.51 vs. 2.41 mmol/L) and ALP (248.00 vs. 111.13 IU/L) levels compared with controls (p=0.01 and p<0.001 respectively, maximum likelihood estimation). Logistic regression analysis demonstrated that high serum calcium and phosphate levels during PD were associated with a 4.5 and 2.9 fold increase in the risk of developing EPS respectively. Conclusion: High levels of calcium and phosphate in patients on PD were identified to be risk factors for EPS development. Possible reasons for this may be an imbalance of pro-calcifying factors and calcification inhibitors promoting peritoneal calcification which increases peritoneal stiffness. Mechanical alterations may trigger, unregulated fibrosis and subsequent development of EPS. Improved management of secondary hyperparathyroidism during PD may ultimately diminish the EPS risk.